Evaluación de bloques nutricionales con la adición de tres niveles de harina de remolacha (Beta vulgaris) como suplemento energético en la alimentación de cuyes (Cavia porcellus) en la fase de crecimiento-engorde - Lascano Barros, Gabriela Lizbeth (2022)
This research was carried out in the province of Tungurahua, in the canton of Ambato, to evaluate the nutritional blocks with the addition of 3 levels of beet flour as an energy supplement in feeding guinea pigs growth-fattening phase. A methodology with a completely randomized factorial design (CRD) was used to study one factor; where 40 male guinea pigs with an average weight of 350 grams were used, divided as follows: T0 (control), T1 (addition of 2% beet meal), T2 (addition of 4% beet meal) and T3 (addition of 6% beet meal). When evaluating the zootechnical parameters, no significant statistical difference (p > 0.05) was found between the means of the treatments according to Duncan's test. The results were obtained and considered the use of beet meal with a protein of 10.11% and fiber of 12.39%. It was concluded that the use of beet meal is suitable for animal consumption and can be carried out by employing nutritional blocks. The use of nutritional blocks with the addition of 6% beet meal is recommended, taking into account that feeds consumption, weight gain, and carcass yield are higher than the other treatments, together with an alfalfa-based diet.